Pemanfaatan Limbah Baglog Jamur Tiram (Pleurotus sp.) dan Sayur Organik Dengan Perlakuan Fermentasi Menggunakan Effective Microorganism (EM4) Sebagai Media Tumbuh Cacing Sutera (Tubifex sp.) - Andrew Setiawan Rusdianto; Deni Septian Ardana (JOFE : Journal of Food Engineering, 2023)
The silk worm is feed for fish seeding. The silk worm supplying for that necessity majority still got from river and ground drain. But the river and drain flow that polluted obstruct the silk worm population, growth, and development in wild nature. Another that every rainy season the river and drain flow being swift until washed away the majority silk worm until decrease the silk worm for that necessity. Caused by it necessary conducted the silk worm breeding, in this moment use oyster mushroom media waste and organic vegetable as breeding media, with fermented use EM4 for increase the silk worm biomass. This research uses Complete Random Design with 2 factor (oyster mushroom media waste and organic vegetable) and 3 treatments (0%, 25%, 50% EM4 gift). Then the research data result is analyzed use 1 way Anova test P<5%. If analysis result is show effect, then data analysis continued to 5% LSD test to know that resulted effect is significant or no. This research result is show that cultivation media type with EM4 gift that result the highest silk worm biomass is organic vegetable media with 25% EM4 gift result 11,76 gram the silk worm wet mass with 0,196 gram/day daily growth average speed, and 6,82 gram the silk worm dry mass with 0,11 gram/day daily growth average speed.